(3eHGOF GdeMGSHIs - (3fYje(B, (3OgeTs; (3eMeO CHh fUGQ(B, s ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 1999)
(3GdeHGOF GdeMGSHjI hGdbhGFe GdeGdjI, GdOhQI GdeMGSHjI, YedjGJ GdHVGYI dOi GdeTGQjY GdJLGQjI, GdJShjGJ GdeMGSHjI heHOC GdebGHdI, GdfbOjI aj GdUfOhb hGdHfc, GdPee GdeOjfI hChQGb GdbHV, GdGSJKeGQGJ GdeGdjI bUjQI GdCLd HGdCSe hGdSfOGJ, GdeNRhf, GdCUhd GdKGHKI, bGFeI GdJShjI (B((3hQbI GdYed(B) (3hGbaGd GdMSGHGJs
(3GdeQGLY U(B.425s
Keywords: (3GdGSJKeGQs; (3GdSfOGJs; (3GdeMGSHIs